Autologous hematopoietic stem cell transplantation in remission consolidation of acute myeloid leukemia with initially unfavorable prognostic factors - G. D. Petrova (Onkogematologiâ, 2016)
Introduction. The role of autologous hematopoietic stem cell transplantation (autoHSCT) in adult patients with acute myeloid leukemia (AML) with poor prognosis factors is not completely defined.Purpose: to present the results of a multicenter prospective study of autoHSCT efficacy in AML patients with initially unfavorable prognostic factors.Materials and methods. From 2007 to 2014, 42 patients with primary AML with one or more poor prognosis factors were included in the study. AutoHSCT was performed in 16 patients (9 women) aged 20–57 years (median 38 years) without available compatible allogeneic (related or unrelated) donor. In order to identify the role of different prognostic factors the long-term results were analyzed.Results. With a median follow up of 49 months (range 5–86 months) 5-years overall survival, event-free survival and relapse-free survival were 47, 47 and 51 %, respectively. Rate of mortality associated with transplantation in 100 days and 2 years after autoHSCT reached 0 and 6 %, respectively. AML relapse was observed in 44 % of patients. Favorable prognostic influence of total body irradiation in conditioning regimens on the overall survival has been identified (р = 0.045).Conclusion. AutoHSCT in AML patients with initially poor prognosis factors has a long-term anti-tumor effect. In the absence of a fully compatible allogeneic donor, autoHSCT may be considered as an alternative treatment.